Anti-Crisis Measures in Bulgaria in Large Migration Flows - Penkova, Tsvetomira (Research Papers, 2022)
The object of this research is the anti-crisis measures in Bulgaria related to illegal migration. The focus is on the migration crisis in 2015 – 2016. The main goal is to analyze the need to improve and prepare the country for large migration flows. It is especially important to consider the basic and key concepts – migration and anti-crisis measures. As well as process analysis. The main task of this article is to show that in the event of a large migration wave, the country will need to take new anti-crisis measures.
Keywords: Migration flows; Refugee wave; Anti-crisis management; Bulgaria